Question
Wed April 20, 2011 By: Gunjan Singh

trigonometry

Expert Reply
Fri April 22, 2011
we know the law of tangent ;
(c-b)/(c+b)=(tan1/2(C-B))/(tan1/2(C+B))..........1
So,
(c-b)/(c+b)tan(A/2)={(tan1/2(C-B))/(tan1/2(C+B))}tan(A/2)
                                 ={(tan1/2(C-B))/(tan(?/2-A/2))}tan(A/2) ........(A+B+C=?)                       
                                 ={(tan1/2(C-B))/(cot(A/2)}tan(A/2)..................(tan(?/2-A/2)=cot(A/2))   
                                 ={(tan1/2(C-B))tan(A/2)}tan(A/2).....................(1/cot(A/2)=tan(A/2))
                                 =(tan1/2(C-B))tan2(A/2)
 

Related Questions
Wed May 11, 2016

find the value of  x

Wed May 11, 2016

Sin

Ask the Expert